CASTING SHADOWS: Shading Digital Elevation Models Using Ray Tracing. - Gill, Kevin M. (InSight: Rivier Academic Journal)
This article describes the algorithms and methods used in generating shadows on digital elevation models. These include formulas that are very common in computer graphics applications and are often provided by specific frameworks (i.e. OpenGL). The basics of model rendering are covered from the structure of the source data to the interpolation of hypsometric/bathymetric tint colors. Hillshading is a common component seen on elevation models and is covered with the formulas provided either in the text or in the appendix. The primary algorithm presented is the calculation of shadows using ray tracing. The basic components of the method are presented leaving the reader free to provide any number of enhancements that may be needed in their own software. The methods are based on code from the jDem846 open source project managed by the author. Code listings are provided below and available in full online.